Partial uterine perforation and ovarian embedment of misplaced intrauterine device: a case report - Kaushik, Abhishek; Rajpurohit, Dalpat S.; Chaturvedy, Kirti; Vishnoi, Sunil; Panduranga, Anish H.; Kammar, Asaf Ali K.; Nandvanshi, Girija (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Intrauterine devices (IUDs) are the commonest form of contraceptive method in use globally. IUDs like other methods of contraception may be associated with its own complications. The major risk includes uterine perforation with embedment, migration, and/or expulsion. A 35 year old female who had a history of postpartum IUD insertion 10 years ago was referred to our institute with complains of severe lower abdominal pain and vomiting since 10 days. Transabdominal and transvaginal ultrasound (TAS/TVS) were done. Ultrasound led to the final diagnosis of ovarian embedment of the IUD. Laparotomy with IUD removal was successfully performed. This case report highlights one of the rare complications of IUD migrating to the left ovary in a patient presenting with lower abdominal pain. In a patient with history an IUD insertion in situ, lower abdominal pain and missing threads on examination should wary the gynaecologist to the possibility of total or partial transmigration of the device into the pelvis or abdomen.